The TEL patch of telomere protein TPP1 mediates telomerase recruitment and processivity - Nandakumar, Jayakrishnan (2012)
Human chromosome ends are capped by shelterin, a protein complex that protects the natural ends from being recognized as sites of DNA damage and also regulates the telomere-replicating enzyme, telomerase(1–3). Shelterin includes the heterodimeric POT1-TPP1 protein, which binds the telomeric single-stranded DNA tail(4–9). TPP1 has been implicated both in recruiting telomerase to telomeres and in stimulating telomerase processivity (the addition of multiple DNA repeats after a single primer-binding event)(9–14). Determining the mechanisms of these activities has been difficult, especially because genetic perturbations also tend to affect the essential chromosome end-protection function of TPP1(15–17). Here we identify separation-of-function mutants of TPP1 that retain full telomere-capping function in vitro and in vivo, yet are defective in binding telomerase. The seven separation-of-function mutations map to a patch of amino acids on the surface of TPP1, the TEL patch, that both recruits telomerase to telomeres and promotes high-processivity DNA synthesis, indicating that these two activities are manifestations of the same molecular interaction. Given that the interaction between telomerase and TPP1 is required for telomerase function in vivo, the TEL patch of TPP1 provides a new target for anti-cancer drug development.